2021
DOI: 10.3389/fimmu.2021.680441
|View full text |Cite
|
Sign up to set email alerts
|

EGR3-HDAC6-IL-27 Axis Mediates Allergic Inflammation and Is Necessary for Tumorigenic Potential of Cancer Cells Enhanced by Allergic Inflammation-Promoted Cellular Interactions

Abstract: The objective of this study was to investigate mechanisms of allergic inflammation both in vitro and in vivo in details. For this, RNA sequencing was performed. Early growth response 3 gene (Egr3) was one of the most highly upregulated genes in rat basophilic leukemia (RBL2H3) cells stimulated by antigen. The role of Egr3 in allergic inflammation has not been studied extensively. Egr3 was necessary for passive cutaneous anaphylaxis (PCA) and passive systemic anaphylaxis (PSA). Egr3 promoter sequences contained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…Diverse studies carried out in mouse models suggested the involvement of these molecules (miR-155, miR-154-5p, miR-26a, miR-26b, miR-122a-5p, miR-135-5p and miR-182-5p) in the allergic inflammatory processes behind anaphylaxis [176][177][178][179][180]. In human samples, the analysis of miRNA levels demonstrated variations in these molecules during this pathological event.…”
Section: Micrornasmentioning
confidence: 98%
See 1 more Smart Citation
“…Diverse studies carried out in mouse models suggested the involvement of these molecules (miR-155, miR-154-5p, miR-26a, miR-26b, miR-122a-5p, miR-135-5p and miR-182-5p) in the allergic inflammatory processes behind anaphylaxis [176][177][178][179][180]. In human samples, the analysis of miRNA levels demonstrated variations in these molecules during this pathological event.…”
Section: Micrornasmentioning
confidence: 98%
“…For instance, miR-26a and miR-26b regulate COX 2 levels, a key enzyme in this process and in the release of the cytokines involved [177]. Conversely, an antiinflammatory effect of miR-182-5p has been reported as it reduces the levels of IL-27, a cytokine involved in allergic inflammation [180]. Similarly, miR-122 was also found to participate in the inhibition of this process through the regulation of suppressor of cytokine signaling 1 (SOCS1) and Janus kinase 2 (JAK2), both of which control the production of the anti-inflammatory mediator TGF-β [178].…”
Section: Communication Between Microenvironments: Mirnas and Evsmentioning
confidence: 99%
“…Erg3 is an immediate early gene that has been implicated in a plethora of biological events ranging from tumor development to allergy and from drug abuse to psychiatric disorders such as schizophrenia [78][79][80][81] . Its expression is likely regulated by multiple pathways although underlying mechanisms are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The NFκB-Egr3 complex formed by Egr3 and the NF-κB subunits p50 and p65 may regulate the expression of in ammatory genes in the pathogenesis of CHD. Moreover,the NFκB-Egr3 complex can activate the promoter sequence of IL-6 and IL-1β gene expression [23,30] . The results of this study showed that serum Egr3 level was correlated with IL-6 levels.…”
Section: Discussionmentioning
confidence: 99%